Influence of photocatalysts mass on photocatalytic degradation of mixture of pharmaceuticals by oxide ZnO/TiO2 nanopowder - Štrbac Dragana (Proceedings of the International Symposium on Analytical and Environmental Problems, 2018)
In this paper, the efficiency of photocatalytic degradation of mixture of pharmaceuticals (naproxen, diclofenac, ketoprofen and ibuprofen) in the aqueous medium using nanoparticle photocatalysts powder ZnO/TiO2, activated by UV radiation, has been examined. It has been shown that the degradation of diclofenac, ketoprofen and ibuprofen takes place efficiently regardless of the mass of the catalyst. Naproxen has proven to be the most resistant pharmaceutical and degradation constants are calculated for naproxen only, which may be used as guidelines in further research. Keywords: photocatalysis, pharmaceuticals, naproxen, diclofenac, ketoprofe, ibuprofen, ZnO/TiO2.